Differences of sympathetic and parasympathetic modulation in major depression - Schumann, Andy; Andrack, Caroline; Bär, Karl-Jürgen (Progress in neuro-psychopharmacology & biological psychiatry, 2017)
Inconsistent results have been reported with respect to cardiac autonomic function in major depression. The aim of our study was to investigate autonomic function in various branches of the autonomic nervous system in order to better understand parasympathetic and sympathetic modulation in the disease. We investigated 29 unmedicated patients suffering from major depression (MD) in comparison to matched control subjects (gender, age, BMI). The autonomic assessment at rest included values of heart rate variability (HRV), blood pressure variability (BPV), baroreflex sensitivity (BRS), respiration, skin conductance (SC) as well as the calculation of pupillary diameter and the unrest index (PUI). Results were compared by means of a multivariate analysis of variance. In a classification analysis, we identified suitable parameters for patient - control separation. Finally, to analyze interrelations of pupillometric parameters and autonomic indices, we estimated Pearson correlation coefficients and fitted a linear regression model. Apart from a significantly increased heart rate (75±12 vs. 65±6min−1, p<0.001) and decreased BRS (14±13 vs. 20±15ms/mmHg, p<0.05), we observed a lack of significant differences in HRV and BPV analysis between patients and controls. However, pupillary diameter (left: 4.3±0.9 vs. 3.8±0.6, p<0.01; right: 4.3±0.9 vs. 3.7±0.6mm, p<0.01) and PUI (left: 14.8±6.0 vs. 10.7±4.5mm/min, p<0.01; right: 14.1±5.5 vs. 10.7±4.8mm/min, p<0.01), as well as the level (left: 7.3±6.2 vs. 4.3±4.4 μS, p<0.05) and fluctuations of skin conductance (left: 4.2±4.1 vs. 2.5±3.6, p<0.05; right: 4.2±4.4 vs. 2.6±3.2, p<0.05) were significantly different. The classification accuracy was 88.5% with high specificity (e=92.9%) and sensitivity (s=83.3%) including heart rate, PUI and skin conductance. HRV indices correlated to PUI in controls but not in patients. Our data add evidence to the current debate on autonomic function in major depression. We suggest that diverse results are mainly caused by methodological shortcomings, in particular by the application of HRV assessment only, which misses changes of sympathetic modulation. The application of broader analyzing tools will clarify the pattern of autonomic function in depression and ultimately its role in cardiac morbidity and mortality. •Comprehensive investigation of the autonomic nervous system including various branches•Sympathetic predominance in patients indicated by skin conductance and pupil size, but not by heart rate variability.•Highly accurate classification of patients and controls considering heart rate, pupillary unrest and skin conductance